2014
DOI: 10.1016/s0140-6736(13)62062-0
|View full text |Cite|
|
Sign up to set email alerts
|

Reduction of adverse effects from intravenous acetylcysteine treatment for paracetamol poisoning: a randomised controlled trial

Abstract: Chief Scientist Office of the Scottish Government.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
175
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(182 citation statements)
references
References 23 publications
4
175
0
3
Order By: Relevance
“…A two-hour time frame was selected because it has been observed that many single overdoses were ingested over a time period of up to two hours, (13) and this time frame is reasonably narrow for the Rumack-Matthew nomogram to be used to predict the risk of hepatotoxicity based on timed plasma paracetamol levels. Supratherapeutic doses ingested over a time period > 2 hours were considered as staggered overdose or repeated supratherapeutic ingestion, which was collectively referred to as 'staggered ingestion' in this study.…”
Section: Methodsmentioning
confidence: 99%
“…A two-hour time frame was selected because it has been observed that many single overdoses were ingested over a time period of up to two hours, (13) and this time frame is reasonably narrow for the Rumack-Matthew nomogram to be used to predict the risk of hepatotoxicity based on timed plasma paracetamol levels. Supratherapeutic doses ingested over a time period > 2 hours were considered as staggered overdose or repeated supratherapeutic ingestion, which was collectively referred to as 'staggered ingestion' in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Because of these reactions, recent studies have investigated modified protocols that extend the loading dose. While these studies show decreased side effects requiring interruption of treatment, they have not been adequately powered to ensure efficacy at the suggested modified dosing (Bateman et al 2014c). …”
Section: Clinical Managementmentioning
confidence: 99%
“…Artificial support systems employ hemodialysis with adsorption to charcoal or albumin to remove toxins, while bioartificial systems use human or porcine hepatocytes for plasma filtration. These systems are currently used only in investigative trials, but meta-analyses have shown reduced bridging to transplantation in patients with acute-on-chronic liver failure with artificial systems and improved mortality in ALF with bioartificial systems (Craig et al 2010a;Bateman et al 2014c). …”
Section: Liver Support Systemsmentioning
confidence: 99%
“…Aiming to reduce adverse events, a clinical trial published in 2014 evaluated the efficacy and safety of a shorter 12 hour NAC regimen compared to the standard 20.25 regimen in UK [31]. The trial randomly allocated patients with acute paracetamol overdose to four arms, either the standard intravenous NAC regimen or a shorter 12 hour modified protocol, with or without 4 mg of ondansetron IV given as pretreatment.…”
Section: Reducing Adverse Effects From Intravenous Nacmentioning
confidence: 99%